INOVASI PEMASARAN TANAMAN MELON HIDROPONIK DALAM GREENHOUSE MELALUI MARKETPLACE FACEBOOK - R. Marsuki Iswandi; Dhian Herdhiansyah; Asriani Asriani; La Ode Midi; Lukman Yunus; Yusriadin Yusriadin; Nafilawati Nafilawati (Jurnal Abdi Insani, 2023)
Griya Melon Kendari UMKM has been established since 2019. Even though it has been around for a long time, the UMKM still uses traditional promotion and marketing methods. The promotion and marketing process for the product is still simple, with consumers who want to buy it coming to MSMEs to buy some of the hydroponic melon plants. Because of this, MSMEs cannot sell widely, even though this has been done in several locations in Kendari City. The aim of this PKM activity is to increase knowledge and skills in marketing innovations for hydroponic melon plants in greenhouses through the Facebook marketplace. The activity partner is UMKM Griya Melon Kendari. The activity was held on August 15, 2023, and was attended by 20 participants. Activity plan: (1) preparation stage (team meetings, partner meetings, and preparation of facilities and equipment); and (2) implementation stage Training using a demonstration approach method. The results of the pre-test evaluation showed that the training participants' knowledge and skills regarding marketing hydroponic melon plants via the Facebook marketplace were 50 percent. Meanwhile, the results of the post-test evaluation after the training activity on marketing hydroponic melon plants in greenhouses via the Facebook marketplace showed an increase of 90 percent among the training participants. The results of the activity show that the process of using the Facebook marketplace feature is very influential as a medium for promotion and marketing of hydroponic melon plant products. The implementation of the Facebook marketplace has greatly influenced the sales value of hydroponic plant products at Griya Melon Kendari MSMEs in Southeast Sulawesi. This is realized by taking steps to sell via the Facebook marketplace. ​